BREAKDOWN OF INTER-GENERATIONAL RELATIONS AS A RESULT OF THE SOCIAL FUNCTION OF THE FAMILY - Dovranova Oysulton Dovrankulovna (Web of Journals Publishing, 2023)
This article sociologically analyzes how important the social functions of the family are in the breakdown of intergenerational relations.
Keywords: family, intergenerational relationship, sociological view, family household